2015
DOI: 10.1111/1753-6405.12220
|View full text |Cite
|
Sign up to set email alerts
|

Growing Up in New Zealand cohort alignment with all New Zealand births

Abstract: Objective: To compare the birth characteristics of the Growing Up in New Zealand cohort with those of all New Zealand (NZ) births over a similar time period, and to describe cohort alignment to current NZ births. Method:The Growing Up in New Zealand longitudinal study recruited 6,846 children from before birth via their pregnant mothers who were residing in the greater Auckland and Waikato regions during 2009 and 2010. Data were collected from mothers antenatally and six weeks after their expected delivery dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 13 publications
3
106
3
1
Order By: Relevance
“…Third, comparisons of the survey data with the 2007 and 2009 FNES should be interpreted with caution due to sampling and population differences. Previous research has shown the similarity of the child population in the Auckland, Counties Manukau and Waikato District Health Board regions to the national population (43) and we expect that the results of the present survey will be pertinent to ECE services outside the study population. Further analyses planned for the survey data include: a dietary assessment of child-care menus; source, cost and preparation of food provided by services; physical activity strategies and equipment; and nutrition and physical activity programme participation.…”
Section: Discussionmentioning
confidence: 68%
“…Third, comparisons of the survey data with the 2007 and 2009 FNES should be interpreted with caution due to sampling and population differences. Previous research has shown the similarity of the child population in the Auckland, Counties Manukau and Waikato District Health Board regions to the national population (43) and we expect that the results of the present survey will be pertinent to ECE services outside the study population. Further analyses planned for the survey data include: a dietary assessment of child-care menus; source, cost and preparation of food provided by services; physical activity strategies and equipment; and nutrition and physical activity programme participation.…”
Section: Discussionmentioning
confidence: 68%
“…21 Our findings confirm that these disparities in access to antenatal care persist and, unlike these earlier studies, do so in a sample that is generalisable to the national birth cohort. 8 Most women in this study (92% 'most conservative', 86% 'reasonably conservative' estimates) engaged a LMC within the recommended time of the first ten weeks. The most recent MoH maternity consumer survey 3 reports that 30% of women choose their LMC within the first six weeks of pregnancy, with a further 53% in the first seven to 12 weeks (ie 83% of women under 12 weeks) and that M aori and Pacific women were less likely than European women and women from other ethnic groups to choose a LMC in the first six weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 76%
“…In the Waikato DHB region, the landscape setting varies widely and so does the climate with mean annual temperatures ranging from less than 8 °C at higher elevations to 14 °C in the low-lying areas [21]. The 6853 children enrolled represent 11% of national births during the recruitment period, and the characteristics of the study cohort closely align with those of recent national births [22]. Ethical approval for the study was granted by the NZ Ministry of Health Northern Y Regional Ethics committee and written informed consent provided by all participants for study participation and data linkage.…”
Section: Methodsmentioning
confidence: 99%